Excessive Gestational Weight Gain in the First Trimester among Women with Normal Glucose Tolerance and Resulting Neonatal Adiposity - Josefson, Jami L. (J Perinatol, 2016)
OBJECTIVE: To assess whether weight gain above or below Institute of Medicine (IOM) recommended amounts in an ethnically diverse obstetric population with normal glucose tolerance is associated with differences in neonatal adiposity. STUDY DESIGN: In this prospective cohort study, healthy women with normal glucose tolerance based on the International Association of Diabetes and Pregnancy Study Groups guidelines were enrolled. Gestational weight at multiple time points were collected. Neonatal adiposity was measured by air displacement plethysmography at 24-72 hours of life. Analyses included Fisher's exact test, ANOVA, and a trajectory analysis using a group-based weight gain trajectory model with a censored normal distribution. RESULT: Overweight and obese women were more likely to exceed IOM weight gain guidelines. Regardless, there was no significant difference in %body fat of neonates born to mothers who either met or exceeded gestational weight gain guidelines. Gestational weight gain timing influenced neonatal anthropometrics: women who gained excessively by the first prenatal visit had neonates with significantly higher birth weight (3.91 kg vs. 3.45 kg, p<0.001), and %body fat (13.7% vs. 10.9%, p=0.0001) compared to women who had steady, moderate gestational weight gain. CONCLUSION: Avoidance of excessive gestational weight gain in the first trimester may prevent high amounts of neonatal adiposity.